ELEVATED TROPONIN IN AN ATHLETE - MYOCARDIAL INFARCTION OR A PHYSIOLOGICAL OCCURRENCE? - Janković, Tamara; Ðorðević, Stefan (Halo 194 Scientific Journal of Emergency Medicine, 2024)
INTRODUCTION Measurement of troponin values is a basic laboratory analysis in every patient with a chest pain. Increase of blood troponin is a highly specific indicator of AMI, but other diagnoses also can result in an increase of troponin,and it’s known that intense physical activities can lead to troponin release.The objective is to present a patient who, due to a collapse while running, was brought to the hospital, where further diagnostics revealed a huge increase of troponin and later an AMI was excluded. CASE REPORT A patient collapsed during a race and lost consciousness.In the laboratory analysis, increasing values of Troponin were found, but ACS was excluded. It was concluded that elevated troponin was probably a consequence of physical activity. CONCLUSION Any chest pain and simptoms that may indicate ACS requires special attention from an emergency physician and must be familiar with different pathologies and consequences of intense physical activity.